A cost analysis of a sports-based sexual health education programme for adolescent girls in South African schools. Issue 10 (29th September 2022) - Bango, Funeka; Pike, Carey; Coakley, Chelsea; Bekker, Linda-Gail; Cleary, Susan
Abstract: Studies have shown that school-based sexual health promotion interventions can improve adolescent sexual and reproductive health outcomes. However, there has been insufficient evidence on the cost and cost-effectiveness of such programmes, driving poor and inconsistent investment and prioritization. This paper analyses the costs of the SKILLZ Health for Girls programme, a sports-based sexual education intervention targeted at adolescent girls in the secondary school environment. Costs were collected alongside a cluster-randomized trial, including 38 secondary schools in Cape Town, South Africa. The analysis was conducted from a provider (multi-sector) perspective and used a mixed-methods costing approach. We developed a cost data collection tool to compile cost information from one-on-one interviews, administrative data and non-participant observations of the intervention. Costs were analysed for 2019, representing a full academic year of programme implementation. The intention-to-treat analysis revealed an average cost per learner per session of $9.92, and the cost per learner reached was estimated at $69.43. Sensitivity analysis indicated that these costs were sensitive to the participation rates of the learners who did not complete the intervention. The cumulative cost for the scale-up scenario for the Western Cape Province based on the base-case analysis (maximizing coverage of schools but only including 30% of eligible learners within schools) was estimated at $5 311 453.00 for a 3-year period, which exceeds the provincial conditional grant allocation dedicated to the human immunodeficiency virus and acquired immune deficiency syndrome (life skills education) for the same period, yet is comparable to the expenditure for a similar donor-funded programme within the province. The study's results will contribute to decision-making for implementing sexual education interventions in schools in South Africa and similar contexts.